FORMULASI TABLET EKSTRAK DAUN SAMBILOTO (Andrographis paniculata N.) SECARA KEMPA LANGSUNG DENGAN KOMBINASI MANITOL – SORBITOL SEBAGAI BAHAN PENGISI - Lutfiana Kusumawati (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2015)
It has been conducted research about Tablets Formulation of Creat (Andrographis paniculata N.) Leaves Extract in Directly Compressed with Combination of Manitol-Sorbitol as Filler Materials. The result of test shows that every formula fulfills test conditions of quality for uniformity of weight, brittleness, size measure and hardness, such as those which qualified by Farmacope Indonesia and other monographs. Statistical test using Ansira (Variance Design Analysis) indicates that usage of filler materials combinations mannitol – sorbitol for formula I, II and III respectively 50% : 50%, 75% : 25% dan 25% : 75%, yield no significant effect for physical quality tablet